Transformational Leadership on Teacher Performance Through the Mediating Role of Motivation - Sarinah Sarinah; Ade Taufan; Mardalena Mardalena; Saukani Saukani; Puji Tri Aryanti; Ruwaiza Sasmita (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
The purpose of this study is to investigate the impact of the principal's transformational leadership on school performance, as mediated by teachers' work motivation at MTsN 1 Merangin. This study employs a quantitative method as well as explanatory research. Primary data is collected using questionnaires for three relevant variables, while secondary data is gathered from school records, textbooks, and periodicals. The sample employed in this study was non-probability purposive sampling, with a total of 51 teachers. Smart PLS v.3 software runs the PLS-SEM data analysis algorithms. This study found that the principal's transformative leadership had a considerable positive direct effect on teacher performance (coefficient 0.208, t-count 1.660, a standard deviation 0.126, p-value 0.045 < 0.05). It demonstrates that transformational principle leadership has a substantial impact on teacher performance. The principal's transformational leadership has a considerable direct and beneficial effect on teachers’ motivation (coefficient 0.675, t-count 12.979, a standard deviation 0.05, p-value 0.000 < 0.05. It indicates a significant effect of transformative leadership on teacher motivation. Next, there was a considerable beneficial direct influence of teachers' motivation on teacher performance (coefficient 0.634, t-count 5.574, a standard deviation 0.114, p-value 0.000 < 0.05). It indicates a statistically significant influence of teacher motivation on performance. Last, motivation can operate as a mediator (coefficient 0.428, standard deviation 0.087, t-count 4.888, p-value 0.000 < 0.05). motivation mediates transformational leadership to teacher performance. So, the school principal was encouraged to have more intellectual stimulation, care, and inspire teachers, as well as other indicators of transformational leadership, to boost teacher motivation and performance.